2015
DOI: 10.1007/s11120-015-0107-z
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic model for estimating net photosynthetic rates of cos lettuce leaves under pulsed light

Abstract: Time-averaged net photosynthetic rate (P n) under pulsed light (PL) is known to be affected by the PL frequency and duty ratio, even though the time-averaged photosynthetic photon flux density (PPFD) is unchanged. This phenomenon can be explained by considering that photosynthetic intermediates (PIs) are pooled during light periods and then consumed by partial photosynthetic reactions during dark periods. In this study, we developed a kinetic model to estimate P n of cos lettuce (Lactuca sativa L. var. longifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…The cultivation experiment examining the effect of red and blue LED lights on cos lettuce growth demonstrated that the pattern containing single irradiation with blue light caused the stem extension and the longer cycle of alternating irradiations with red and blue light also led to promote stem extension (Jishi et al, 2015). Thus, day length and single irradiation time of blue light are strongly associated with growth acceleration, factors that we intend to focus on in future experiments in order to establish the optimal irradiation pattern.…”
Section: Effects Of Simultaneous or Alternating Irradiation Of Red Anmentioning
confidence: 97%
“…The cultivation experiment examining the effect of red and blue LED lights on cos lettuce growth demonstrated that the pattern containing single irradiation with blue light caused the stem extension and the longer cycle of alternating irradiations with red and blue light also led to promote stem extension (Jishi et al, 2015). Thus, day length and single irradiation time of blue light are strongly associated with growth acceleration, factors that we intend to focus on in future experiments in order to establish the optimal irradiation pattern.…”
Section: Effects Of Simultaneous or Alternating Irradiation Of Red Anmentioning
confidence: 97%
“…A kinetic model to estimate Pn was developed by considering that photosynthetic intermediates were pooled during light periods and then consumed by partial photosynthetic reactions during dark periods [25]. According to this model, they quantitatively estimated the effects of pulsed light frequency and duty ratio on photosynthetic rates of cos lettuce leaves.…”
Section: Photosynthetic Capacity Measured At Pulsed Lightmentioning
confidence: 99%
“…Flashing light studies on single leaves of land plants or microalgal cultures with low light attenuation potential can identify the biological boundary, and may be described as a function of frequency (f) and duty cycle (ø), i.e. f(ø,f) [17,18]. For example, Jishi et al [17] identified such function of the flashing light effect for lettuce (Lactuca sativa).…”
Section: Biological Boundariesmentioning
confidence: 99%
“…f(ø,f) [17,18]. For example, Jishi et al [17] identified such function of the flashing light effect for lettuce (Lactuca sativa). Interestingly, their model also fits the photosynthetic performances of microalgal cultures with low biomass concentrations (< 0.1 g L -1 ) or short light path lengths (<1-2 cm) and for land plants (e.g.…”
Section: Biological Boundariesmentioning
confidence: 99%